How the emergence of the omicron variant may change people’s attitudes toward the COVID-19 pandemic - Yang, Yong (Frontiers in Psychology, 2022)
Background This study aims to examine people’s attitudes toward the COVID-19 pandemic before and after the emergence of the omicron variant. Methods Data were collected between November 15 and December 14, 2021, and three attitudes were included, namely, the negative influence on daily life, concerns of infection risk, and prediction of the ending of the pandemic. Results The majority of people perceived that daily life was at least somewhat negatively influenced by the COVID-19 pandemic, and they worried at least once a week about infection risk. After the emergence of the omicron variant, the perceived negative influence and concern of infection risk decreased slightly while the prediction of ending increased significantly. People who were infected by COVID-19 perceived more negative influence and more concern of infection risk, but were more optimistic about the ending of the pandemic. People who did not get a vaccine perceived less negative influence and less concern of infection risk, but were more pessimistic about the ending of the pandemic. The attitudes varied significantly by individual and contextual characteristics. Conclusion The emergence of omicron significantly increased people’s predicted ending time of the pandemic but did not change people’s perception of the pandemic’s negative influence on daily life and concern of infection risk.